From Assembly Line to Industry 4.0: The Evolution of Manufacturing - RITESH UPADHYAY, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Beginning with the development of the assembly line by Mr. Henry Ford, the industrial sector has seen a considerable shift since the late 18th century. The industry has continually changed to be more effective, efficient, and increase productivity, beginning with the mass production of standardized items in the 20th century and ending with the talk about automation and robots in 2017. The industrial 4 th revolution will combine cutting-edge technology like artificial intelligence, machine learning, smart factories, big data analytics, and the internet of things to create a more effective and connected environment. This paper will discuss the turning points, trends and patterns, and problems in the development of manufacturing starting from the assembly line to Industry 4.0. In its later part, the paper will discuss the potential pros that the latest Industry offers, that include customization by the customers, sustainability, and protection of employees. Moreover, it discusses the essential methods for businesses to adopt and succeed. Ultimately, the paper will conclude that Industry 4.0 represents a transformative shift in the manufacturing sector that will revolutionize the way humans conceive, fabricate, and utilize various products